Public awareness towards antibiotics use, misuse and resistance in Saudi community: A cross-sectional population survey - Izzeddin A. Bdair, Ola A. Bdair, Gladys M. L. Maribbay, Donia Elzehiri, Eman S. Hassan, Amor D. Tolentino, Mahmoud Metwally Emara, Ehab Kamal Ali, Reda M. Abdelmeged, Mayada O. Fadul (Journal of Applied Pharmaceutical Science, 2024)
Antibiotics (ABs) resistance is a worldwide health issue. However, there is a lack of awareness toward the proper use of ABs. This study was designed to assess the awareness of antibiotic usage and antibiotic resistance (ABR) among the public. A population-based survey was executed from September to November 2023. A validated questionnaire was administered to 600 participants. Data were analyzed through Statistical Package for the Social Sciences version 25. Multivariate regression was administered to identify associated factors with awareness. The results revealed a high prevalence of ABs consumption. The public knowledge of ABs was suboptimal where (50.2%) of the participants had sufficient knowledge. Moreover, it is worth highlighting that respondents hold a generally positive attitude (72.3%) and satisfactory practice (69.7%). Participants who are older, male, educated, married, and employed typically have significantly higher mean scores in knowledge, attitude, and practice. Public awareness about proper antibiotic usage and ABR is a vital public health concern. Considering the current study’s findings, ongoing educational activities should emphasize the importance of improving the public’s judicious use of ABs, which may help curb the spread of ABR. Educational campaigns to improve health literacy regarding dispensing, purchasing, prescribing, and using ABs are recommended particularly for the target groups.
Keywords: Antibiotics resistance, awareness, public health, self-medication, Saudi Arabia